Method for transferring film onto support substrate
By locally over-injecting hydrogen ions in Smart CutTM technology to form an early separation starting point, the problem of surface roughness variation caused by spontaneous separation is solved, and the surface finish improvement at high and low frequencies of the SOI structure is achieved, which improves the film's Manufacturing quality.
Patent Information
- Application Number
- CN202380030863.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-01
- Filing Date
- 2023-03-20
- Publication Date
- 2024-12-17
AI Technical Summary
In Smart CutTM technology, the variation in surface roughness of films caused by spontaneous separation, especially at high and low frequencies, affects the final quality of the SOI structure, and existing finishing methods are difficult to effectively reduce surface roughness.
By locally over-injecting hydrogen ions into the buried fragile plane of the donor substrate, an early separation start point is formed, ensuring a short breaking time and repeatability, thereby improving roughness over the entire surface of the film, using a third dose of hydrogen Ion implantation is less than three times the first dose, and the local excess area is located in the central area, with a surface area between 10 μm2 and 2 cm2, and the third energy is lower than the first energy, forming excellent surface quality.
After the stack structure finishing, the low micro-roughness and a small amount of high-roughness local areas are achieved, which significantly improves the surface finish of the film, improves the manufacturing quality of the SOI structure, and ensures consistent surface quality at high and low frequencies. sex.
Smart Images

Figure CN119156697A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of microelectronic devices and semiconductors. Specifically, the present invention relates to a method for TM A method for transferring a thin film onto a supporting substrate, the thin film exhibiting improved roughness after separation. Specifically, the transfer method can be used to manufacture SOI structures. Background Art
[0002] Known Smart Cut TM The technology is used to manufacture SOI (silicon on insulator) structures and more generally for thin film transfer. The technology is based on the formation of a fragile plane embedded in a donor substrate by injecting a light substance into the substrate; the embedded fragile plane defines the thin film to be transferred together with the front side of the donor substrate. The donor substrate and the support substrate are then joined at their respective front sides to form a bonded structure. The assembly is advantageously carried out by direct bonding, by molecular adhesion (i.e., without involving adhesive materials): a bonding interface is thus established between the two assembled substrates. By thermal activation, the growth of microcracks in the embedded fragile plane can lead to spontaneous separation along the plane, resulting in the transfer of the thin film to the support substrate (forming a stacked structure, such as SOI type). The remaining donor substrate can be reused for subsequent film transfer. After separation, the stacked structure is usually subjected to a finishing treatment to restore the crystalline quality and surface roughness of the transferred thin film. These treatments are known to involve oxidation or smoothing heat treatments (under neutral or reducing atmospheres), chemical cleaning and / or etching and / or chemical mechanical polishing steps. Various inspection tools can be used to inspect the entire surface of the thin film.
[0003] When separation in the embedded fragile planes is spontaneous, significant variations are observed in the surface roughness of the transferred film at both high frequencies (micro-roughness) and low frequencies (ripples, local areas of high roughness, spots, etc.) These variations are visible when inspecting the film in the final structure and are particularly measurable via the inspection tools described above.
[0004] Recall that you can use Surfscan from KLA-Tencor TM Inspection tool to map the surface roughness of the film after finishing ([ Figure 1 ]). The level of roughness and potential patterns (spots, dense areas, etc.) are measured or made apparent by measuring the diffuse background noise ("haze") corresponding to the intensity of light scattered by the surface of the film. -1 Up to 10μm -1The haze signal varies linearly with the square of the RMS surface roughness over a spatial frequency range of . For more information on this large area roughness inspection and evaluation technique, please refer to F. Holsteyns' article "Seeing through the haze" (Yield Management Solutions, Spring 2004, pp. 50-54).
[0005] [ Figure 1 The figures in ] show the surface roughness of two thin layers transferred from two bonded structures that were identically processed until finishing. Figure (A) shows a peripheral zone of residual roughness, called the "dense zone" (ZD); Figure (B) has no dense zone at all. More pronounced spots (M) are also visible in Figure (A). The average and maximum roughness (expressed in ppm haze) also differ between the two Figures (A) and (B). [ Figure 1 ] shows the final quality and roughness variation of the film, which is mainly due to the variation of the surface roughness after separation (high and low frequencies).
[0006] Therefore, in order to improve the final quality of the transferred films, in the case of spontaneous separation by thermal activation, it remains important to reduce the surface roughness of these layers after transfer, regardless of the spatial frequency.
[0007] Purpose of the Invention
[0008] The present invention proposes a transfer method that uses a local excess of light material in the buried fragile plane of the donor substrate, ensuring early initiation of fracture and obtaining improved roughness over the entire surface of the film after separation to achieve excellent surface quality after the finishing stage of the stacked structure. The method is particularly beneficial for the manufacture of SOI structures. Summary of the invention
[0009] The present invention relates to a method for transferring a thin film onto a supporting substrate, the method comprising the following steps:
[0010] - providing a bonded structure comprising a donor substrate and the support substrate, the donor substrate and the support substrate being assembled by direct bonding with their respective front faces following a bonding interface extending along a main plane, the donor substrate comprising an embedded fragile plane, the embedded fragile plane being substantially parallel to the main plane and formed by a step of implanting a light substance, the step of implanting a light substance comprising co-implanting hydrogen ions of a first dose and a first implantation energy and helium ions of a second dose and a second implantation energy,
[0011] - applying a fracture heat treatment to the bonded structure in order to induce a spontaneous separation along the embedded brittle plane, associated with the growth of microcracks in said plane due to thermal activation, which separation results in the transfer of the film from the donor substrate to the supporting substrate.
[0012] The excellence of this process lies in that the step of implanting light matter also includes locally implanting hydrogen ions with a third dose and a third energy to form an excess local area in the buried fragile plane, and the third dose corresponds to more than three times the first dose, so that the excess local area constitutes a separation starting point.
[0013] Advantageous features according to the invention (alone or in any feasible combination):
[0014] ● the third energy is lower than the first energy;
[0015] The local excess region is located in a central region of the donor substrate according to the main plane;
[0016] ●The first dose is 1E16 / cm 2 + / -40%, the second dose is 1E16 / cm 2 + / -40%, and the third dose is between three times (not including three times) and seven times the first dose, preferably about four times the first dose;
[0017] ● The local excess area has a thickness of 10 μm in the main plane 2 With 2cm 2 The surface area between
[0018] The donor substrate and / or the support substrate has an insulating layer at least on their respective front sides, the insulating layer forming a buried insulating layer adjacent to the bonding interface in the bonding structure;
[0019] • The thin film from the donor substrate is single crystal silicon, and the support substrate comprises single crystal silicon to form a stacked SOI structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Other features and advantages of the present invention will become apparent from the following detailed description of the invention with reference to the accompanying drawings, in which:
[0021] [ Figure 1 ][ Figure 1 ] shows two representative surface roughness images of two transferred films from two bonded structures that were identically processed prior to finishing using conventional methods; TM Check the tool to get these two graphs;
[0022] [ Figure 2 ][ Figure 2] shows a plurality of bonded structures that were identically processed prior to finishing according to conventional methods (similar to reference [ Figure 1 ] as a function of film surface roughness and rupture time for films with different bonding structure types;
[0023] [ Figure 3 ][ Figure 3 ] shows a bonding structure used in an intermediate stage of the transfer method according to the present invention;
[0024] [ Figure 4 ][ Figure 4 ] shows a stacked structure obtained by the transfer method according to the present invention and the remaining part of the donor substrate;
[0025] [ Figure 5 ][ Figure 5 ] shows different localized hydrogen ion implantation tests and associated results;
[0026] [ Figure 6 ][ Figure 6 ] shows a photograph of a stacked structure obtained by the transfer method according to the present invention;
[0027] Some of the drawings are schematic diagrams which, for the sake of readability, are not drawn to scale. In particular, the thickness of the layers along the z-axis is not proportional relative to the lateral dimensions along the x-axis and the y-axis.
[0028] The same reference numerals in the drawings or the specification may be used for the same type of elements. DETAILED DESCRIPTION
[0029] The present invention relates to a method for transferring a thin film onto a supporting substrate to form a stacked structure. As mentioned in the introduction, such a stacked structure may be of SOI type, comprising a thin silicon surface layer, an intermediate insulating layer and a silicon supporting substrate. The supporting substrate may optionally include other functional layers, such as a charge trapping layer, for example for SOI structures designed for radio frequency applications. However, the transfer method described herein is not limited to the manufacture of SOI and may be applied to many other stacked structures in the fields of microelectronics, microsystems and semiconductors.
[0030] The transfer method according to the present invention is based on Smart Cut TMTechnology. When separation in an embedded fragile plane is spontaneous, the fracture time (i.e., the time after separation occurs during the thermal fracture anneal) can be different between multiple identically processed bonded assemblies subjected to the same anneal in the same furnace. The fracture time (TF) depends on multiple parameters related to the formation of the embedded fragile plane, the fracture anneal, the properties of the bonded structure, etc. Applicants have noticed that for similarly prepared bonded structures subjected to the same fracture anneal, separation occurring at a short fracture time (TFc) results in a film having lower high-frequency surface roughness (micro-roughness) in the final stacked structure (i.e., after transfer and finishing) than separation occurring at a longer fracture time (TF1), as shown in [ Figure 2 ]. In addition, long rupture times induce localized areas of very high roughness (called dense zones ZD) at the edges of the film after rupture, which is not the case or is rarely the case when the rupture time is short. Figure 1 ], even after finishing, this dense area will degrade the quality and roughness of the film.
[0031] Therefore, the transfer method according to the invention aims to initiate spontaneous separation in the embedded fragile planes in an early (short break time) and reproducible (low break time dispersion between multiple similar bonded structures) manner in order to significantly improve the surface roughness of the transferred film.
[0032] To this end, the transfer method comprises first providing a bonding structure 100 comprising a donor substrate 1 and a support substrate 2, which are assembled by direct bonding with their respective front faces (1a, 2a) following a bonding interface 3 ([ Figure 3 ]).
[0033] The donor substrate 1 is preferably in the form of a wafer having a diameter of 100 mm, 150 mm, 200 mm, 300 mm or even 450 mm and having a thickness typically between 300 μm and 1 mm. It comprises a front side 1a and a back side 1b. The surface roughness of the front side 1a is chosen to be less than 1.0 nm RMS, preferably even less than 0.5 nm RMS (measured by atomic force microscopy (AFM), for example on a 20 μm×20 μm scan). The donor substrate 1 may be made of silicon or any other semiconductor or insulating material that may be of interest for thin film transfer (e.g. SiC, GaN, LiTaO3, etc.).
[0034] It should also be noted that the donor substrate 1 may include one or more additional layers 12, such as an insulating layer, at least on its front side 1a. The thickness of the additional layer may range from a few nanometers to several hundred nanometers. Figure 3 ], after assembling the donor substrate 1 and the supporting substrate 2, the additional layer 12 becomes a buried intermediate layer in the bonding structure 100.
[0035] The donor substrate 1 comprises a fragile buried plane 11 which delimits the thin film 10 to be transferred. TM As is well known in the art, such a fragile buried plane 11 can be formed by a step of injecting a light substance. The light substance is injected into the donor substrate 1 at a determined depth consistent with the thickness of the target film 10. They will form microcavities distributed in the film around the determined depth, and the film is substantially parallel to the front surface 1a of the donor substrate 1, or parallel to the plane (x, y) in the figure. For simplicity, the film is called a buried fragile plane 11.
[0036] In particular, in the context of the present invention, the implantation step comprises co-implanting hydrogen ions at a first dose and a first implantation energy and helium ions at a second dose and a second implantation energy.
[0037] The implantation energy of the light species is selected so as to reach a certain depth. For example, hydrogen ions will be implanted at a first energy between 10keV and 180keV, and helium ions at a second energy between 20keV and 210keV, to define a thin film 10 having a thickness of the order of 100nm to 1200nm.
[0038] The implanted hydrogen ion dose (or first dose) is usually 1E16 / cm within the specified range of the first implant energy. 2 The implanted helium ion dose (or second dose) is also 1E16 / cm2 within the specified range of the second implant energy. 2 On the order of + / - 40%.
[0039] Advantageously, the helium ions are implanted before the hydrogen ions.
[0040] Recall that before the ion implantation step, an additional layer may be deposited on the front side 1a of the donor substrate 1. This additional layer may consist, for example, of a material such as silicon oxide or silicon nitride. It may be retained for the next assembly step (and form all or part of the intermediate layer of the bonding structure 100), or it may be removed.
[0041] The support substrate 2 is also preferably in the form of a wafer having a diameter of 100 mm, 150 mm, 200 mm, 300 mm or even 450 mm and having a thickness typically between 300 μm and 1 mm. It comprises a front side 2a and a back side 2b. The surface roughness of the front side 2a is selected to be less than 1.0 nm RMS, preferably even less than 0.5 nm RMS (measured by AFM, for example on a 20 μm×20 μm scan). The support substrate 2 may be made of silicon or any other semiconductor or insulating material that may be of interest for thin film transfer. In the context of the present invention, the material constituting the support substrate 2 must be compatible with applying a temperature greater than or equal to 400° C. to the bonded structure 100 resulting from the assembly of the donor substrate 1 and the support substrate 2.
[0042] It should also be noted that the support substrate 1 may include one or more additional layers, such as an insulating layer and / or a charge trapping layer, at least on its front side 2a. The additional layers may have a thickness of a few nanometers to a few micrometers. After assembling the donor substrate 1 and the support substrate 2, they are embedded in the bonding structure 100.
[0043] The assembly between the donor substrate 1 and the support substrate 2 is based on direct bonding by molecular adhesion. As is known per se, this type of bonding does not require adhesive materials, since bonding at the atomic scale is established between the joined surfaces, thereby forming a bonding interface 3. There are several types of molecular adhesion bonding, which differ specifically in their temperature, pressure, atmosphere conditions or treatments performed before contacting the surfaces. Mention may be made of bonding at room temperature with or without prior plasma activation of the surfaces to be assembled, atomic diffusion bonding (ADB), surface activated bonding (SAB), etc.
[0044] The assembly steps may include, before the front sides 1a, 2a to be assembled come into contact, a conventional chemical cleaning sequence (e.g., RCA cleaning), surface activation (e.g., oxygen or nitrogen plasma) or other surface treatments (such as cleaning by scrubbing), which can improve the quality of the bonding interface 3 (few defects, strong adhesion energy).
[0045] Once the bonded structure 100 has been formed, the transfer method according to the invention comprises applying a fracture heat treatment to induce spontaneous separation along the embedded fragile plane 11. The separation results in the transfer of the thin film 10 from the donor substrate 1 to the support substrate 2 to form a stacked structure 110 ([ Figure 4 ]). A remaining part 1' of the donor substrate is also obtained. The heat treatment can usually be carried out in a horizontal furnace at a temperature between 200°C and 400°C (capable of jointly treating a plurality of bonded assemblies 100), in particular for silicon-based bonded structures 100.
[0046] As mentioned above, the step of implanting light substances applied to the donor substrate 1 to form the buried fragile plane 11 includes co-implanting hydrogen ions of a first dose and a first implantation energy and helium ions of a second dose and a second implantation energy. For example, starting from a silicon donor substrate 1 having a diameter of 300 mm (from which a 240 nm thin film 10 is to be obtained) to form a FD-SOI (fully depleted SOI) stacked structure 110, the co-implantation conditions are as follows: 40 keV-1E16 / cm 2 Helium ions were introduced and then ionized at 25keV-1E16 / cm 2 Hydrogen ions are introduced. A further layer 12 of silicon oxide is applied to the donor substrate 1 , for example with a thickness of approximately 100 nm.
[0047] As referenced [ Figure 2 ] explained, since the transfer times are more or less short or long and in any case unpredictable, these co-implantation conditions applied to multiple structures lead to different results in terms of post-separation (and post-finishing) surface roughness.
[0048] Therefore, in order to solve the problem of transfer time reproducibility, the method according to the invention provides that the step of implanting the light substance comprises locally implanting hydrogen ions with a third dose and a third energy after or before the co-implantation of helium and hydrogen. This implantation creates a local excess region 11b in the buried fragile plane 11, which is intended to serve as a starting point for early separation in the buried fragile plane 11. This early separation ensures a short break time and therefore ensures an excellent, highly reproducible surface finish of the transferred film 10 during the collective processing of a plurality of bonded structures 100.
[0049] This local implantation is remarkable because the third dose corresponds to more than three times the first dose, which is very significant. In fact, the applicant has noticed that locally implanting the first dose of hydrogen once, twice or even three times is not enough to form a reliable and reproducible separation starting point. When the third dose does not exceed three times the first dose, the local excess area 11b does not repeatedly trigger the start of separation: this maintains a significant variability in the fracture time and therefore maintains undesirable fluctuations in the surface state of the transferred film 10. In fact, contrary to all expectations, a third dose less than or equal to three times the first dose is not enough to trigger a fracture in the embedded fragile plane 11 before other potential starting points: that is, a local bonding defect at the unbonded peripheral edge area of the bonding interface 3 or the bonding structure 100.
[0050] [ Figure 5 The table in ] shows that the energy of the samples was 40 keV and 25 keV respectively and the energy of the samples was 1E16 / cm 2 and 1E16 / cm 2The fracture time and post-separation surface finish results (in ppm haze) of various local hydrogen ion implantation tests in the case of an embedded fragile plane 11 formed by co-implanting helium and hydrogen with a dose of 1.547 W. The hydrogen ion implantation energy (or third energy) in the local excess region 11b is 25 keV, the same as the first implantation energy. The separation annealing is performed at 350°C.
[0051] These results confirm that, contrary to expectations, an excess of less than or equal to three times the first dose (H) does not have the expected effect of early separation onset. The break times of structures 1 to 3 remain high and fluctuate, and the surface finish does not improve over the typical values obtained without local excess (about 26 ppm + / - 2 ppm of "haze") ("Ref" structure).
[0052] When the locally implanted third hydrogen dose is equal to five times (structure 4) or even seven times (structures 5, 6) the first dose, the excess local region 11b effectively acts as a fracture initiation point: it induces a shorter reproducible fracture time and improves the surface finish in terms of repeatability and haze amplitude (reduced by 12% to 25% compared to the structure without excess local region 11b). Early fracture ensures low micro-roughness (high spatial frequency) and few, if any, local regions of high roughness (also called dense regions ZD).
[0053] It should also be noted that at the level of the excess regions 11 b, the local surface roughness of the film 10 is lower than in other regions of the layer 10, and therefore no specific features are generated that could affect the quality of the final stacked structure 110. For example, for [ Figure 5 ], the haze values for structures 5 and 6 shown in FIG. 1 are of the order of 19 ppm (compared to a total haze value of 20.9 ppm or 20.7 ppm on the plate).
[0054] Preferably, the first dose (H) is 1E16 / cm 2 In + / - 40% of cases, the third dose is strictly greater than three times the first dose and less than or equal to seven times the first dose; even more preferably, the third dose is between four and five times the first dose.
[0055] This specific overselection has been found to be extremely effective in forming early and reproducible fragmentation initiation sites.
[0056] Beyond an upper limit of seven times the first dose, there is a significant risk of bubbles on the surface of the donor substrate 1. The presence of these bubbles can then cause bonding defects at the bonding interface 3 and degrade the quality of the bonded structure 100.
[0057] The excess region 11b can be located in the center (along the main plane (x, y)) of the donor substrate 1, at the periphery or in an intermediate region between these two extremes. Its location in the center brings the advantage that the separation wave propagates from the center to the edge of the bonded structure 100, which greatly limits the amplitude of spots M or other disruption waves (roughness and low-frequency ripples) on the surface of the transferred film 10.
[0058] The local excess region 11b can occupy tens of μm in the main (x, y) plane. 2 With a few cm 2 The area between the 2 With 2cm 2 between.
[0059] The local implantation can be performed by a mechanical mask featuring a hole with a surface area equal to the target surface area of the local excess region 11b. Alternatively, masking techniques such as deposition, photolithography and etching of masking layers can be used, or by controlled scanning of a hydrogen ion beam.
[0060] Finally, advantageously, the local implantation of hydrogen ions is performed at a third energy different from the first energy. In fact, it has been shown that the thickness of the film 10 transferred in the region 10c corresponding to the local excess region 11b is greater than the thickness of the film 10 anywhere else. Therefore, the third implantation energy (related to the local implantation of H) is preferably chosen to be lower than the first energy.
[0061] For the sake of illustration, [ Figure 6 ] shows a SOI 110 type stacked structure (similar to [ Figure 5 ] is a photograph of structure 5 or 6). The visible surface is the free surface 10a of the thin film 10 after transfer. Due to the thickness difference of the layer 10 locally in the region 10c, the region 10c (corresponding to the local excess region 11b) is different in color from the rest of the thin film 10. In this example, the thickness difference of the thin film 10 between the region 10c and the rest of the plate is of the order of 29nm. Within the range of implantation energies implemented in these examples, it can be estimated that the transferred silicon thin film 10 increases by approximately 8nm to 8.5nm per keV. In [ Figure 6 ] In the example shown in FIG. 1 , the third implantation energy is therefore preferably set to be 3.5 keV lower than the first implantation energy, i.e., 36.5 keV.
[0062] Adjusting the third implant energy further improves the surface finish of the transferred film 10 by avoiding local thickness differences in the region 10c.
[0063] Due to the presence of specific local excess areas 11b that act as early separation starting points in an effective and reproducible manner, the transfer process according to the invention provides an improved surface quality 10a of the transferred film 10 compared to SOI structures obtained from bonded structures processed by conventional processes, because the surface 10a presents no or very few spots M or dense areas ZD. The level of micro-roughness ("haze") of the face of the film 10, before or after smoothing, is also lower than the roughness level obtained by conventional methods.
[0064] Another important advantage is the reproducibility of these results over multiple bonded structures 100 processed together.
[0065] Of course, the invention is not limited to the embodiments described and variant embodiments may be envisaged without departing from the scope of the invention as defined by the claims.
Claims
1. A method for transferring a thin film (10) onto a supporting substrate (2), the method comprising the following steps: - providing a bonding structure (100), comprising a donor substrate (1) and a support substrate (2), the donor substrate and the support substrate being assembled by direct bonding with their respective front faces (1a, 2a) following a bonding interface (3) extending along a main plane (x, y), the donor substrate (1) comprising an embedded fragile plane (11), the embedded fragile plane (11) being substantially parallel to the main plane and formed by a step of implanting a light substance, the step of implanting a light substance comprising co-implanting hydrogen ions of a first dose and a first implantation energy and helium ions of a second dose and a second implantation energy, - applying a fracture heat treatment to the bonded structure (100) so as to induce spontaneous separation along the embedded fragile plane (11), the spontaneous separation being associated with the growth of microcracks caused in the embedded fragile plane (11) due to thermal activation, the separation causing the transfer of the film (10) from the donor substrate (1) to the support substrate (2), The method is characterized in that the step of implanting light matter further comprises locally implanting hydrogen ions of a third dose and a third energy, thereby forming an excess local area (11b) in the embedded fragile plane (11), wherein the third dose corresponds to more than three times the first dose, so that the excess local area constitutes a separation starting point.
2. The transfer method according to the preceding claim, wherein the third energy is smaller than the first energy.
3. Transfer method according to one of the preceding claims, wherein the local excess region (11b) is located in a central region of the donor substrate (1) along the main plane (x, y).
4. The transfer method according to claim 1, wherein the first dose is 1E16 / cm 2 + / -40%, the second dose is 1E16 / cm 2 + / -40%, and the third dose is three times (not including three times) to seven times the first dose, preferably four times the first dose.
5. The transfer method according to claim 1, wherein the surface area of the local excess region along the main plane (x, y) is 10 μm 2 Up to 2cm 2 .
6. A transfer method according to one of the preceding claims, wherein the donor substrate (1) and / or the support substrate (2) have an insulating layer (12) at least on one side of their respective front sides (1a, 2a), which insulating layer forms an embedded insulating layer adjacent to the bonding interface (3) in the bonding structure (100).
7. The transfer method according to the preceding claim, wherein the thin film (10) from the donor substrate (1) is made of single-crystal silicon and the support substrate (2) comprises single-crystal silicon to form a stacked SOI structure (110).
